The effect of morphology on electrochemical hydrogen evolution reaction of ReSe2 nano-structures. (18th July 2022) - Sultana, Fozia; Mushtaq, Muhammad; Ferdous, Tabassum; Wang, Jiahui; Lin, Ma; Zaman, Abid; Althubeiti, Khaled; Aljohani, Mohammed; Yang, Qing
Abstract : Transition metal dichalcogenides (TMDs), such as rhenium diselenide, have currently attracted a lot of attention as one of the novel candidates of the TMD family. Abstract : Transition metal dichalcogenides (TMDs), such as rhenium diselenide, have currently attracted a lot of attention as one of the novel candidates of the TMD family. However, sample fabrication remains a significant problem due to poor electrochemical performance, and synthesizing ReSe2 with outstanding tailored features to encounter the high-level demands of noble metal replacement persists a challenge. As a result, we suggest a method for the production of ReSe2 with controllable morphologies by simply changing the Re : Se ratio of the precursors. Herein, two distinct morphologies i.e. nanoparticles and nanobelts of ReSe2 were synthesized using a hot injection approach. Phase study and modes of vibrations of both samples were investigated using X-ray diffraction crystallography (XRD) and Raman spectroscopy. Scanning electron microscopy (SEM) and transmission electron microscopy (TEM) confirmed ReSe2 nanoparticle and nanobelt morphologies. The nanobelts ReSe2 outperformed by achieving a current density of 10 mA cm −2 at an over-potential of 96 mV whereas ReSe2 nanoparticles attained a current density of 10 mA cm −2 at 174 mV. The remarkable electrocatalytic performance of ReSe2 nanobelts is due to their unique morphology, which allows for quick charge transfer kinetics and incredible stability even after 1000 CV cycles.